The Effect of Suplementation of Sambiloto (Andrographis paniculata) Extract Through Drinking Water on Total Erythrocytes and Total Leucocytes of Broiler - Muhammad Mirandy Pratama Sirat; Madi Hartono; Purnama Edy Santosa; Ratna Ermawati; Teo Achmad Fauzi; Nur Aini; Fina Arzakiyah; Imam Widodo; Teo Achmad Fauzan (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
The aim of this study was to determine the effect and the best dose of Sambiloto (Andrographis paniculata) extract supplementation on total erythrocytes and total leukocytes in broilers. The study was conducted for 6 months, May – October 2021. Maintenance and treatment of broilers for 30 days was carried out at the Karang Anyar Farm broiler cage unit in Karang Anyar Village, Jati Agung District, South Lampung Regency, Lampung Province. The experimental study used a completely randomized design with five treatments. Each treatment consisted of 25 broilers of the Cobb CP 707 strain which were divided into 5 cages, so a total of 125 broilers in 25 cages. Sambiloto (Andrographis paniculata) as an immunomodulator was added to drinking water with different doses according to broiler body weight, namely drinking water without a liquid extract of Sambiloto (Andrographis paniculata) (P0); drinking water with Sambiloto liquid extract 0.05 cc/kg BW (3 mg/kg BW) (P1); 0.1 cc/kg BW (6 mg/kg BW) (P2); 0.2 cc/kg BW (12 mg/kg BW) (P3); 0.4 cc/kg BW (24 mg/kg BW) (P4). Total of 25 blood samples from 30-day-old broiler were taken through the brachial vein using a 3 mL syringe and stored in a 5 mL EDTA tube. Calculation of total erythrocytes and total leukocytes at the Palembang Health Laboratory and then the data were analyzed descriptively. The highest total erythrocyte in broilers was P0, the lowest was P4, the mean total erythrocyte was within normal limits for all treatments. The highest broiler leukocyte total was P2, the lowest was P3, the average total leukocyte for all treatments was above the normal range. The active compound in Sambiloto (Andrographis paniculata) is andrographolide which can act as an immunostimulant for specific and non-specific immune functions through NK cells, macrophages, and cytokine induction. The flavonoid content in sambiloto will also send intracellular signals to cell receptors to increase its activity when immune system activity is reduced which can increase the production of IL-2 thereby increasing lymphocyte proliferation, increasing the proliferation and differentiation of B and NK cells. The conclusion was that supplementation of Sambiloto (Andrographis paniculata) extract through drinking water can maintain the number of erythrocytes within normal limits and increase the number of leukocytes as an immune response after vaccination with the best supplementation dose in drinking water of 6 mg/kg BW which is equivalent to a volume of 0.1 cc/liquid extract. kg BB broiler.